An electrochemical sensing platform with a molecularly imprinted polymer based on chitosan-stabilized metal@metal-organic frameworks for topotecan detection. - Mehmandoust, Mohammad; Tiris, Gizem; Pourhakkak, Pouran; Erk, Nevin; Soylak, Mustafa; Kanberoglu, Gulsah S; Zahmakiran, Mehmet (My University, 2023)
The present study aims to develop an electroanalytical method to determine one of the most significant antineoplastic agents, topotecan (TPT), using a novel and selective molecular imprinted polymer (MIP) method for the first time. The MIP was synthesized using the electropolymerization method using TPT as a template molecule and pyrrole (Pyr) as the functional monomer on a metal-organic framework decorated with chitosan-stabilized gold nanoparticles (Au-CH@MOF-5). The materials' morphological and physical characteristics were characterized using various physical techniques. The analytical characteristics of the obtained sensors were examined by cyclic voltammetry (CV), electrochemical impedance spectroscopy (EIS), and differential pulse voltammetry (DPV). After all characterizations and optimizing the experimental conditions, MIP-Au-CH@MOF-5 and NIP-Au-CH@MOF-5 were evaluated on the glassy carbon electrode (GCE). MIP-Au-CH@MOF-5/GCE indicated a wide linear response of 0.4-70.0 nM and a low detection limit (LOD) of 0.298 nM. The developed sensor also showed excellent recovery in human plasma and nasal samples with recoveries of 94.41-106.16 % and 95.1-107.0 %, respectively, confirming its potential for future on-site monitoring of TPT in real samples. This methodology offers a different approach to electroanalytical procedures using MIP methods. Moreover, the high sensitivity and selectivity of the developed sensor were illustrated by the ability to recognize TPT over potentially interfering agents. Hence, it can be speculated that the fabricated MIP-Au-CH@MOF-5/GCE may be utilized in a multitude of areas, including public health and food quality.
Keywords: Differential pulse voltammetry; Metal-organic framework application; Molecularly imprinted polymer; Point of care analysis; Topotecan